Forecasting Weekly Stock Price of PT. Aneka Tambang Tbk (ANTM) Using ARIMA Box-Jenkins Method - Wardhani, Andreanne Intan Sulistyo; Yudhanegara, Mokhammad Ridwan (President University, 2024)
Stock price movements in the dynamic economic world require investors and companies to be able to predict future price changes. One method that can be used to predict is Autoregressive Integrated Moving Average (ARIMA). The application of the ARIMA method to forecasting the share price of PT Aneka Tambang Tbk (ANTM) for 4 weeks produces equation obtained from ARIMA (3,1,0) as the best model.